Why are there so many orchid species? - Dodson, Calaway H. (Lankesteriana: International Journal on Orchidology, 2016)
At the present time we have cataloged 3,784 species of orchid naturally occurring in Ecuador, the smallest country in Andean South America. When one considers the size of the country of Ecuador, in comparison with that of Brazil or Colombia, the total numbers seem to express an error on the part of the counter.